Improvement of catalytic activity over Mn-modified CeZrOx catalysts for the selective catalytic reduction of NO with NH3 - Sun, W.; Li, X.; Mu, J.; Fan, S.; Yin, Z.; Wang, X.; Qin, M.; Tade, Moses; Liu, Shaomin (Academic Press, 2018)
A series of MnCeZrOxmixed oxide catalysts were facilely synthesized using the impregnation-NH3·H2O coprecipitation method and tested for selective catalytic reduction (SCR) of NO with NH3. Doping manganese significantly improved the catalytic activity and the best performing SCR catalyst, Mn0.25Ce0.5Zr0.25Ox, was shown to achieve NO conversion > 80% in the temperature range (60–350 °C), with the denitration effect up to 50% at room temperature (conditions: [NO] = [NH3] = 500 ppm, [O2] = 5 vol%, He as balance, flow rate = 100 mL/min, GHSV = 40, 000 h-1). Characterization of the catalyst using BET, XRD, XPS, H2-TPR, and in-situ FTIR proved that the improved SCR activity may be attributed to the large surface area, great reduction ability and increased amount of surface adsorbed oxygen afforded by the introduction of manganese. The SCR reaction mechanisms were also investigated by analyzing in-situ FTIR spectra and the SCR reaction pathway over the Mn0.25Ce0.5Zr0.25Oxcatalyst was shown to mostly follow the E-R mechanism.